Eyetracking experiment using book covers. Visual data analysis in reference to mind space mapping - Osinska, Veslava; Osinski, Grzegorz (Qualitative and Quantitative Methods in Libraries; Vol 9 No 1 (2020): March 2020 Issue, 2020)
The study of the eye movement provides us with the functioning of the visual perception of a human while observing images such as: book illustrations, book covers, posters and other standard publications. The current experiment was performed using the series of collections of book covers. The both configurations of layout and images data set constitute the variables. Due to given results several rules of visual composition for library users are formulated. However, usually the process of analysis relies on determining the areas of the highest concentration of visual attention, which is only interpreted in the frame of mind space mapping paradigm.